Deletion of Fibroblast growth factor 9 globally and in skeletal muscle results in enlarged tuberosities at sites of deltoid tendon attachments. Issue 12 (16th June 2021) - Leek, Connor C.; Soulas, Jaclyn M.; Bhattacharya, Iman; Ganji, Elahe; Locke, Ryan C.; Smith, Megan C.; Bhavsar, Jaysheel D.; Polson, Shawn W.; Ornitz, David M.; Killian, Megan L.
Abstract: Background: The growth of most bony tuberosities, like the deltoid tuberosity (DT), rely on the transmission of muscle forces at the tendon‐bone attachment during skeletal growth. Tuberosities distribute muscle forces and provide mechanical leverage at attachment sites for joint stability and mobility. The genetic factors that regulate tuberosity growth remain largely unknown. In mouse embryos with global deletion of fibroblast growth factor 9 ( Fgf9 ), the DT size is notably enlarged. In this study, we explored the tissue‐specific regulation of DT size using both global and targeted deletion of Fgf9 . Results: We showed that cell hypertrophy and mineralization dynamics of the DT, as well as transcriptional signatures from skeletal muscle but not bone, were influenced by the global loss of Fgf9 . Loss of Fgf9 during embryonic growth led to increased chondrocyte hypertrophy and reduced cell proliferation at the DT attachment site. This endured hypertrophy and limited proliferation may explain the abnormal mineralization patterns and locally dysregulated expression of markers of endochondral development in Fgf9 null attachments. We then showed that targeted deletion of Fgf9 in skeletal muscle leads to postnatal enlargement of the DT. Conclusion: Taken together, we discovered that Fgf9 may play an influential role in muscle‐bone cross‐talk during embryonic and postnatal development. Key Findings: The deltoid tuberosity (DT) is a phenotypic readout for estimating muscle loads during embryonic development in mice. Global loss of FGF9 leads to enlarged DTs. Global loss of Fgf9 led to larger attachment‐site chondrocyte size but reduced cell proliferation at the attachment. Global loss of Fgf9 leads to gene expression differences in muscle, but not bone, and we identified potential mediators of skeletal muscle metabolism in Fgf9null muscle, including downregulated mitochondrial‐related genes associated with oxidative respiration and proton transport. Skeletal‐muscle specific deletion of Fgf9 results in enlarged DTs.